Mechanical analysis of transversal iliac fracture stabilization using dynamic compression plate or screws and PMM in polyurethane bone model - Prada, T. C. [UNESP]; Shimano, A. C.; Chung, D. [UNESP]; Karcher, D. E. [UNESP]; Minto, B. W. (FapUNIFESP (SciELO), 2017)
Pelvic fractures correspond to 20 to 30 % of the fractures observed in dogs. Complete fractures, especially with bone axis deviation should be surgically treated. The mechanical study of surgical techniques is of utmost importance to assess the best way of treating these injuries. This study compared, biomechanically, the use of a dynamic compression plate (DCP) and screws (group 1) or screws and polymethylmethacrylate (PMMA) (group 2) to stabilize an iliac fracture using a static test. Sixteen canine synthetic hemi-pelvises (test specimens) with a transverse iliac osteotomy were used. After fixation with implants, a load was applied to the acetabulum until failure. Group 1 maximal compressive load was 133.9±18.60 N, displacement at yield 21.10±3.59mm and stiffness 125.22±12.25N/mm. Group 2 maximal compressive load was 183.50±27.38N, displacement at yield 16.66±5.42mm and stiffness 215.68±33.34N/mm. The stabilization with polymethylmethacrylate was stronger than dynamic compression plate since it resisted a greater load in all test specimens.
Keywords: Biomechanical; Fracture; Pelvis; Stabilization